UPAYA AUSTRALIAN MARRIAGE EQUALITY DALAM MENEGAKKAN HAM SESUAI RESOLUSI PBB TERKAIT MASALAH SAME SEX MARRIAGE DI AUSTRALIA - Tri Yuliana; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study describes and illustrates the shape of Australian Marriage Equality efforts in upholding human rights in accordance UN resolutions. Australian Marriage Equality is a national organization that embodies the aspirations and voices of LGBT Australia dedicated to removing discriminatory provisions of the Australian Marriage Act 1961 The purpose of this study is to analyze and describe the background of Australian Marriage Equality and the efforts of Australia's efforts to influence policy related to same sex marriage issue appropriate UN resolutions.The author analyzes the case using descriptive research method, which is a study that seeks to explain something through some literature such as books, journals, and websites. The theory that is used in analyzing the australian marriage equality efforts in upholding human rights related issues same sex marriage in Australia is an international organization theory, role theory, and the concept of human rights.The results of this study illustrate the efforts of AME in enforcing human rights policy changes affecting Australia Same sex marriage related problems include lobbying decision makers, conduct regular forums, equality campaign, mardi gras parade and publish the Roadmap to reform that contains a summary of the efforts made by AME. AME funding comes from public fundraising.Keywords: Australian Marriage Equality, Same Sex Marriage, international organizations, roles, and Human Rights